Analisis Komponen Kritis Forklift dengan FMEA-FTA untuk Preventive Maintenance - Robby Wildani; Mokh Hairul Bahri; Asroful Abidin (Jurnal Ilmu Teknik Terapan, 2026)
PT ABC is a company engaged in material handling services, providing heavy equipment rental and maintenance services, with diesel forklifts constituting the majority of its operating units. The company currently operates 18 diesel forklift units in industrial activities, where equipment failure may significantly disrupt production processes, material distribution, and even increase occupational safety risks. This study aims to analyze the critical components of diesel forklifts and formulate proposed preventive maintenance actions using the integrated Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA) methods. The initial stage involved identifying failure modes, evaluating Severity, Occurrence, and Detection, and calculating the Risk Priority Number (RPN) to determine component priorities. The FMEA results identified the highest-priority critical components as the water pump, battery, engine mounting, and wheel cylinder. Furthermore, the FTA results revealed dominant root causes, including component aging, fluid quality degradation, charging system failures, uneven operating routes, and operator-induced shock loads. Based on the identified basic events, the proposed preventive maintenance actions include age-based component replacement, periodic fluid inspection, charging system checks, engine vibration monitoring, and operator training. These recommendations are expected to reduce failure frequency and improve the availability of forklift units.